Prenatal alcohol exposure affects brain function during place learning in a virtual environment differently in boys and girls - Woods, Keri J. (Brain Behav, 2018)
INTRODUCTION: Although performance deficits in place learning have been reported in fetal alcohol spectrum disorders (FASD), neural correlates of these deficits have not been investigated. This functional magnetic resonance imaging (fMRI) study of 57 children (41 alcohol‐exposed; 16 controls; mean age = 9.4 years; 29 boys) examined effects of prenatal alcohol exposure (PAE) on place learning in a virtual environment, the computer‐generated (CG) arena. METHODS: Functional magnetic resonance imaging data were acquired while children passively viewed a recording of an experimenter completing the task. Visible‐target blocks involved navigation to a visible platform. During invisible‐target blocks, the platform appeared only when the experimenter moved over it. After the scan, all children performed a post‐test during which they had to navigate to the location of the invisible platform. RESULTS: Although there were no group differences in post‐test performance for sex or FASD diagnosis, PAE in boys was associated with poorer performance and reduced activation in the parahippocampal gyrus (PHG), precuneus, posterior cingulate, frontal and temporal lobes, caudate, insula, claustrum, lentiform nucleus, and thalamus. By contrast, PAE was not associated with performance or activation in any regions in girls. DISCUSSION AND CONCLUSION: Girls and boys are known to use different navigation strategies. Boys rely more on an allocentric navigational strategy and girls more on landmarks. Poorer recruitment of the PHG, a region known to mediate allocentric navigation, in more heavily exposed boys may explain the observed dose‐dependent place learning deficit. The absence of PAE effects in girls suggests that landmark‐based navigational strategies may be less affected by alcohol exposure.